Effect of ischemic preconditioning on maximal swimming performance - Williams, N.; Russell, M.; Cook, C. J.; Kilduff, L. P. (The Journal of Strength and Conditioning Research, 2021)
The effect of ischemic preconditioning (IPC) on swimming performance was examined. Using a randomized, crossover design, national- and international-level swimmers (n = 20; 14 men, 6 women) participated in 3 trials (Con, IPC-2h, and IPC-24h). Lower-body IPC (4 × 5-minute bilateral blood flow restriction at 160-228 mm Hg and 5-minute reperfusion) was used 2 hours (IPC-2h) or 24 hours (IPC-24h) before a self-selected (100 m, n = 15; 200 m, n = 5) swimming time trial (TT). The Con trial used a sham intervention (15 mm Hg) 2 hours before exercise. All trials required a 40-minute standardized precompetition swimming warm-up (followed by 20-minute rest; replicating precompetition call room procedures) 1 hour before TT. Capillary blood (pH, blood gases, and lactate concentrations) was taken immediately before and after IPC, before TT and after TT. No effects on TT for 100 m (P = 0.995; IPC-2h: 64.94 ± 8.33 seconds; IPC-24h: 64.67 ± 8.50 seconds; Con: 64.94 ± 8.24 seconds), 200 m (P = 0.405; IPC-2h: 127.70 ± 10.66 seconds; IPC-24h: 129.26 ± 12.99 seconds; Con: 130.19 ± 10.27 seconds), or combined total time (IPC-2h: 84.27 ± 31.52 seconds; IPC-24h: 79.87 ± 29.72 seconds; Con: 80.55 ± 31.35 seconds) were observed after IPC. Base excess (IPC-2h: -13.37 ± 8.90 mmol/L; Con: -13.35 ± 7.07 mmol/L; IPC-24h: -16.53 ± 4.65 mmol/L), pH (0.22 ± 0.08; all conditions), bicarbonate (IPC-2h: -11.66 ± 3.52 mmol/L; Con: -11.62 ± 5.59 mmol/L; IPC-24h: -8.47 ± 9.02 mmol/L), total carbon dioxide (IPC-2h: -12.90 ± 3.92 mmol/L; Con: -11.55 ± 7.61 mmol/L; IPC-24h: 9.90 ± 8.40 mmol/L), percentage oxygen saturation (IPC-2h: -0.16 ± 1.86%; Con: +0.20 ± 1.93%; IPC-24h: +0.47 ± 2.10%), and blood lactate (IPC-2h: +12.87 ± 3.62 mmol/L; Con: +12.41 ± 4.02 mmol/L; IPC-24h: +13.27 ± 3.81 mmol/L) were influenced by swimming TT (P < 0.001), but not condition (all P > 0.05). No effect of IPC was see.